Functional magnetic resonance imaging of internet addiction in young adults - Sepede, Gianna (World J Radiol, 2016)
AIM: To report the results of functional magnetic resonance imaging (fMRI) studies pertaining internet addiction disorder (IAD) in young adults. METHODS: We conducted a systematic review on PubMed, focusing our attention on fMRI studies involving adult IAD patients, free from any comorbid psychiatric condition. The following search words were used, both alone and in combination: fMRI, internet addiction, internet dependence, functional neuroimaging. The search was conducted on April 20(th), 2015 and yielded 58 records. Inclusion criteria were the following: Articles written in English, patients’ age ≥ 18 years, patients affected by IAD, studies providing fMRI results during resting state or cognitive/emotional paradigms. Structural MRI studies, functional imaging techniques other than fMRI, studies involving adolescents, patients with comorbid psychiatric, neurological or medical conditions were excluded. By reading titles and abstracts, we excluded 30 records. By reading the full texts of the 28 remaining articles, we identified 18 papers meeting our inclusion criteria and therefore included in the qualitative synthesis. RESULTS: We found 18 studies fulfilling our inclusion criteria, 17 of them conducted in Asia, and including a total number of 666 tested subjects. The included studies reported data acquired during resting state or different paradigms, such as cue-reactivity, guessing or cognitive control tasks. The enrolled patients were usually males (95.4%) and very young (21-25 years). The most represented IAD subtype, reported in more than 85% of patients, was the internet gaming disorder, or videogame addiction. In the resting state studies, the more relevant abnormalities were localized in the superior temporal gyrus, limbic, medial frontal and parietal regions. When analyzing the task related fmri studies, we found that less than half of the papers reported behavioral differences between patients and normal controls, but all of them found significant differences in cortical and subcortical brain regions involved in cognitive control and reward processing: Orbitofrontal cortex, insula, anterior and posterior cingulate cortex, temporal and parietal regions, brain stem and caudate nucleus. CONCLUSION: IAD may seriously affect young adults’ brain functions. It needs to be studied more in depth to provide a clear diagnosis and an adequate treatment.